Hubungan Iklim Terhadap Produksi Serta Pendapatan Petani Karet di Kabupaten Padang Lawas Utara - Nasution, Irwansyah; Siregar, Tumpal H.S.; Pane, Erwin (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2019)
This study examines the relationship of Climate Variables with Rubber Yield And Farmer Income In Three Subdistricts of Padang Lawas Utara.Â  This study aims to (1) to determine the effect of climate variable to rubber yield and, (2) To know the difference of farmer's income in rainy season and dry season. This research was conducted in March until May 2017. The result of research is climatic variable especially rainfall and rainy day very significant for influentialÂ  rubber yields in Three Subdistricts in Padang Lawas Utara. This may indicate that increasing rainfall amounts with higher rainy days cause a decrease in tapping days resulting in reduction of rubber productivity. There results also showed that farmers' income in rainy season difference in dry season whereas farmer income in dry season is higher than rainy season